PROBLEMATIKA PESERTA DIDIK DALAM MENGHAFAL AL QUR’AN DI SW JAMILURROHMAN - LAYLA LAYLA; UNAISAH SOEHARDIN; AGUS SULISTYO (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
Memorizing the Qur’an is a noble activity, yet students often face various challenges. This study aims to analyze the problems encountered by students at Salafiyah Wustho Jamilurrohman in memorizing the Qur’an. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation. The findings reveal that the challenges arise from both internal and external factors. Internal factors include fatigue, boredom, laziness, lack of focus, low motivation, and the habit of not revising (muraja'ah) at home. External factors involve excessive gadget use, difficulties in time management, numerous school assignments, and insufficient family support. To address these challenges, sincere intentions, dedication, and effort from the students are crucial. Additionally, collaboration between teachers and parents is essential to enhance the students' abilities, enabling them to read and memorize the Qur’an more effectively.